098 The adult profile of SUDEP using the epilepsy deaths register. Issue 12 (14th November 2019) - Craig, Donald; Hanna, Jane; Osland, Karen; Kerr, Mike; Thomas, Rhys H
Abstract : Introduction: There is no 'standard' sudden unexpected death in epilepsy (SUDEP). Attention can be focussed on prevention in those thought to be most at risk of SUDEP but every person with epilepsy is at risk. We sought to identify the median profile of the people with a definite SUDEP death. Method: The voluntary Epilepsy Death Register collects information on the circumstances surrounding the death of a person with epilepsy to identify and improve risk factors that contribute to these deaths. 349 post-mortem confirmed individual entries allowed the production of a profile of the composite, median adult patient at risk of SUDEP. Results: The median death would be male (58.5%) aged 19–30 (48.7%) who lives in the family home (73.3%). and currently in work (45.6%). They were diagnosed more than 10 years ago (53.5%), taking antiepileptic medication (90.1%) and under the care of a specialist in epilepsy (76.2%). They were not known to forget medication (56.4%), had not had a recent AED change (58.7%), Their death was unwitnessed (81.0%) and they were found on their back (57.4%). 55.5% of families did not know that epilepsy could kill. Discussion: SUDEP can occur in otherwise well people with epilepsy. SUDEP should be discussed and safety checks embedded for everyone rather than just 'at risk' subgroups.